2017
DOI: 10.1038/srep39515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HDPE and LDPE degradation by fungus, implemented by statistical optimization

Abstract: Plastic in any form is a nuisance to the well-being of the environment. The ‘pestilence’ caused by it is mainly due to its non-degradable nature. With the industrial boom and the population explosion, the usage of plastic products has increased. A steady increase has been observed in the use of plastic products, and this has accelerated the pollution. Several attempts have been made to curb the problem at large by resorting to both chemical and biological methods. Chemical methods have only resulted in further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(134 citation statements)
references
References 42 publications
6
107
0
8
Order By: Relevance
“…Control sample do not show any peak in range 1710-1605 cm −1 , 3 new absorption band appeared at 1658 cm −1 , 1661 cm −1 , 1667 cm −1 which show formation of ketone and aldehyde. Strong absorbance in the region 1650-1860 cm −1 is due to presence of carbonyl compounds, including esters, aldehyde and carboxylic acid as reported by [33]. Between the range of wave number 2700-2200 cm −1 control show 2 peaks only at 2281 cm −1 and 2260 cm −1 which is decreased as well as increased at 2272 cm −1 , 2285 cm −1 , 2283 cm −1 , 2346 cm −1 and 2348 cm −1 showed formation of carbonyl addition with ammonium group.…”
Section: Ftir Resultsmentioning
confidence: 67%
“…Control sample do not show any peak in range 1710-1605 cm −1 , 3 new absorption band appeared at 1658 cm −1 , 1661 cm −1 , 1667 cm −1 which show formation of ketone and aldehyde. Strong absorbance in the region 1650-1860 cm −1 is due to presence of carbonyl compounds, including esters, aldehyde and carboxylic acid as reported by [33]. Between the range of wave number 2700-2200 cm −1 control show 2 peaks only at 2281 cm −1 and 2260 cm −1 which is decreased as well as increased at 2272 cm −1 , 2285 cm −1 , 2283 cm −1 , 2346 cm −1 and 2348 cm −1 showed formation of carbonyl addition with ammonium group.…”
Section: Ftir Resultsmentioning
confidence: 67%
“…In the study of (Ojha et al, 2017) the FE-SEM images confirmed that the two fungal strains (Penicillium oxalicum and Penicillium chrysogenum) have been able to break down the complex polymer of polyethylene of both HDPE and LDPE into its monomeric forms. The grooves and cracks further confirm the fragility brought about to the plastic sheets on treating the sheets with fungal cultures.…”
Section: A B C D Ementioning
confidence: 76%
“…As references, the stretching band from ν(-CH 2 -) bonds (which do not undergo deformation by weathering), and the band from ν(C=O) (attributed to oxidation compounds generated due to polymer degradation) were chosen. 3,4,31 The obtained band ratios showed reductions of oxidation products of 25 and 76% when Zn 2 Al-NO 3 and Zn 2 Al-N-AB LDH were used as fillers in LDPE to produce the nanocomposite. This can mean that Zn 2 Al LDH has a protective effect against polyethylene oxidation, where the presence of the organic anion more efficiently inhibits the formation of carbonyl groups during weathering.…”
Section: Accelerated Aging Test (Weathering)mentioning
confidence: 96%
“…This degradation is usually induced by factors such as the ultraviolet (UV) radiation in sunlight, high temperatures, presence of photodegradative enhancers, additives and even by the effects of its own molecular weight, which is problematic due to the usage of this polymer, e.g., in electric cables frequently exposed to weathering factors. [1][2][3][4][5][6] To avoid such problems, anti-oxidants and stabilizers are normally used to improve the resistance, but impurities generated during the polymer processing can also increase its degradation. 1 Layered double hydroxides (LDHs) are a typical class of layered materials, frequently called hydrotalcite-like materials.…”
Section: Introductionmentioning
confidence: 99%